Hubungan Status Gizi dengan Kejadian Anemia pada Ibu Hamil di Puskesmas Abepura - Isrojenoveta Retsanboy; Elisabet Bre Boli; Diyah Astuti Nurfa’izah; Oktliana Pasangka (Yayasan Literasi Sains Indonesia, 2025)
Anaemia in pregnancy constitutes a significant global public health issue, influenced by various risk factors such as maternal age and nutritional status. Nutritional issues during pregnancy impacts maternal and fetal health, necessitating careful consideration. An insufficient diet in the antenatal period can predispose to maternal malnutrition, subsequently affecting anaemia. The research was conducted to explore the correlation between nutritional status with anaemia’s prevalence among women in pregnancy at the Abepura Primary Care Facility. This research uses a cross-sectional approach with a descriptive correlational design. Conducted at Abepura Health Centre. The study population comprised all pregnant women who visited the Abepura Health Centre in 2022, totalling 714, with a sample size of 258. Sampling methodology utilising simple random sampling. Data acquisition through questionnaires derived from cohort studies of pregnant women. The chi-square test yielded a p-value of 0.041, indicating statistical significance at the 0.05 level. This finding suggests a meaningful association maternal nutritional well-being and anaemia’s prevalence at the Abepura Health Centre. The odds ratio obtained is OR 1.672 (CI 95% 1.020-2.742), indicating that pregnant women with poor nutritional status are 1.672 times more at risk of anaemia compared to those with adequate nutritional status. Enhance health service initiatives for pregnant women, particularly for those with anaemia, and closely monitor maternal nutritional well-being to promptly address any cases of malnutrition.